Cognitive cultural intelligence and entrepreneurial alertness: evidence from highly educated, employed immigrants in the USA. Issue 2 (18th February 2022) - Yang, Jie; Yu, Mingchuan; Tang, Jintong; Ma, Jieqiong
Abstract : Purpose: There is a dearth of research on how immigrants' cognitive attributes influence their willingness to be self-employed. To offset this paucity, the current study draws on the insights of social cognitive theory (SCT) to examine the immigrants' entrepreneurial alertness. Design/methodology/approach: The authors hired Qualtrics to recruit educated, working immigrants in the USA and tested the hypotheses using a sample of 555 highly educated, employed immigrants from 92 home countries. Findings: This study finds that immigrants' cognitive cultural intelligence (CQ) contributes to entrepreneurial alertness in a positive way. In addition, immigrants' perceived environmental differences and global identity positively moderate the relationship between cognitive CQ and entrepreneurial alertness. Originality/value: This research provides a clear picture of how cognitive CQ impacts immigrants' entrepreneurial alertness; thus, the findings of this study offer ample implications for policymakers. By applying SCT, the current study extended research on immigrants' entrepreneurial alertness by shifting the focus from their individual (e.g. demographic background) or family characteristics to their cognitive attributes. This study suggests that policymakers and entrepreneurship education programs in the U.S.A. should consider offering various types of cultural training programs.